Obesity, dieting, and multiple sclerosis - Russell, Rebecca; Langer-Gould, A.; Gonzales, E.G.; Smith, J.B.; Brennan, Vanessa; Pereira, Gavin; Lucas, R.M.; Begley, Andrea; Black, Lucinda (ELSEVIER SCI LTD, 2020)
Background: Obesity is common in the United States and is associated with a higher risk of relapse and comorbidities, and increased disease progression, in people with MS. Methods: We examined the prevalence of overweight and obesity in the MS Sunshine Study, a matched case-control study of multiple sclerosis in Southern California (470 cases, 519 controls). We reported the proportion of participants who adopted a specific diet for nutrition or weight loss purposes, and identified independent predictors of dieting. Results: In the total population, 32% and 37% were overweight and obese, respectively. Case participants were no more likely to adopt a specific diet for nutrition or weight loss purposes than control participants (10% and 11%, respectively). Being obese, younger, female or non-Hispanic were independently associated with dieting. Conclusion: Despite the evidence that obesity can worsen MS prognosis, and the high prevalence of overweight/obesity, case participants were no more likely to adopt a specific diet than control participants. Improved nutrition education may help people with MS make healthy dietary changes for nutrition or weight loss purposes.